MEMBANGUN DATABASE TERDISTRIBUSI DALAM SISTEM PENJUALANPADA PT. ELECTRONIC SOLUTION JAVA MALL SEMARANG ESTABLISHING OF DISTRIBUTION DATABASE IN SELLING SYSTEM AT PT. ELECTRONIC SOLUTION JAVA MALL SEMARANG (Information Technology and Telematics, 2014)
AbstractRapiddevelopment of technologysothattechnologybecomesthe most important factorin the success ofa companyaswell asthePT. Electronic Solutionis acompany engaged inthe sale ofelectronictoolsthat work withwell-knownbrands. Problems thatariseinsuch systemsislimitedandalsothe consumerswhocomeclientcompanycan notcontrol thesale ofits products directly. This new systemis builtwiththe PHPprogramming languageandMySQLdatabase. Tofurtheroptimize the performance ofthe system, the newsystemisimplementedwitha distributeddatabasemultimasterreplicationmethod. Withthe application ofthismethod, the system performance will be maximizedbecause itwillhavetwoserversthat are connected, integratedsync so thatif oneserver goes down, the otherservercan stillfunctionnormally.Keywords: Distributed Database, Multimaster Replication.